Effects of Digital Science Teaching Materials on Conceptual Understanding and 21st Century Skills: A Metaanalysis - Aprina maharani ZAN; Asrizal; Rose Amnah; Helma; Hidayati (Postgraduate, University of Mataram, 2023)
Innovative learning can improve students' 21st century skills. However, previous research states that students' 21st century skills such as critical thinking, creativity, collaboration and communication are still low. The solution to this problem is to analyze learning using electronic teaching materials. The aim of this research is to analyze the magnitude of the influence of a number of similar studies on students' 21st century skills. The research method can be classified as meta-analysis. In this meta-analysis method, the effect size of each similar study is determined and hypotheses are tested from a number of similar studies. In this research, 20 similar articles from national and international journals were analyzed. From the results of the analysis it can be stated that science teaching materials have a positive effect on 21st century skills based on the type of teaching materials, level of education and 21st century skills. Therefore, the use of science teaching materials is effective in improving students' 21st century skills both in terms of various types of teaching materials, level of education, and subjects.